Danang initial risk assessment. - Danang PC; PEMSEA (Quezon City, Philippines Danang People's Committee, Danang, City, Vietnam and GEF/UNDP/IMO Regional Programme on Building Partnerships in Environmental Management for the Seas of East Asia (PEMSEA), 2004)
PEMSEA Technical Report no. 10